Adrenal Rest Tumor of the Liver Preoperatively Diagnosed as Hepatocellular Carcinoma. (19th June 2017) - Enjoji, Megumu; Sanada, Katsuya; Seki, Ryota; Ito, Takashi; Maeda, Masato
Abstract : Background. Hepatic adrenal rest tumors are rare and show similar findings to hepatocellular carcinoma (HCC). It is difficult to distinguish an adrenal rest tumor from HCC due to radiological similarity. We report a case of an adrenal rest tumor in the liver that mimicked HCC radiologically. Case Presentation. A 67-year-old female was referred to our hospital due to the finding of a hepatic mass. Enhanced computed tomography revealed a 17 mm well-defined tumor that was enhanced in the arterial phase and washed out in the portal and delayed phase in the posterosuperior subsegment of the right hepatic lobe, and HCC was suspected. We performed a subsegmental resection of the liver. Microscopic findings showed that the tumor was composed of pale cells, and tumor cells were aligned in alveolar or fascicular arrangements in a similar manner to features of adrenocortical tissue. Immunohistochemically, the tumor expressed synaptophysin and CD56. The final histopathologic diagnosis in this case was an adrenal rest tumor of the liver. Conclusions. An adrenal rest tumor is similar to HCC in radiological findings. This hepatic tumor should be added to the list of radiological differential diagnoses of hypervascular hepatic tumors.